Clavicular Osteomyelitis Secondary to Candida Parapsilosis Infection - Ranjit, Eukesh (Cureus, 2020)
Candida parapsilosis osteomyelitis is a rare diagnosis. Candidal infection can occur via hematogenous or local spread. A localized swelling around a bony structure should raise clinical suspicion. Diagnosis is made by a combination of imaging modalities and biopsy. Anecdotal case reports have been reported in medical literature and treatment guidelines are very limited. Treatment modality includes a combination of surgical debridement and antifungal therapy.